Interplay of cis and trans mechanisms driving transcription factor binding and gene expression evolution - Emily S. Wong (Nature Portfolio, 2017)
“Variation in the noncoding regulatory sequences in the genome plays important roles in human disease and evolution. Here, the authors use F1 mouse hybrids to shed light on the regulatory mechanisms mediating transcription factor binding, chromatin state and gene expression in mammalian cells.”